2001
DOI: 10.2306/scienceasia1513-1874.2001.27.127
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this paper, a mathematical model for the solidification of the semi-crystalline polymers is proposed to predict the size of the crystallites. In addition to the degree of the crystallinity, the size of the crystallites is one of the structural variables, which can shape the mechanical properties of the polymer materials. During the quiescent non-isothermal processes, the mean radius of crystallites is a function of both nucleation and growth process. The density of the potential nuclei is assumed to follow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…A number of researchers4–6 have examined the temperature and crystallization behaviors of molten polymers during cooling through both computer simulation and experimental approaches. Hu et al4 investigated the effect of cooling system design, part thickness, mold thermal properties, coolant temperature, and cycle time on the cyclic variation of mold temperatures with the dual reciprocity boundary element method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A number of researchers4–6 have examined the temperature and crystallization behaviors of molten polymers during cooling through both computer simulation and experimental approaches. Hu et al4 investigated the effect of cooling system design, part thickness, mold thermal properties, coolant temperature, and cycle time on the cyclic variation of mold temperatures with the dual reciprocity boundary element method.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity and coolant temperature were observed to have a considerable effect on the variations in mold temperature values as compared to effects of cycle time and part thickness. Leephakpreeda5 proposed a mathematical model for the solidification of semicrystalline polymers under quiescent nonisothermal crystallization to predict the size of the crystallites. It was suggested that the mean radius of the crystallites was a function of nucleation and growth processes, and the spherulite size increased with increasing cooling rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation